The Sagebrush State, 5th Edition : Nevada's History, Government, and Politics - Bowers, Michael Wayne (Book collections on Project MUSE., 2018)
"Nevada's politics have been formed in large measure by its turbulent history and harsh environment. The Sagebrush State is a readable and insightful explanation of how Nevada's history created its political culture and how its government works today. This volume includes the full text of the state constitution, with extensive annotations of all amendments to the original 1864 document. The fifth edition is updated through 2017 to include information on recent controversial sessions of the legislature."--Provided by publisher.